Edges And Extraction: Evidence From Chichewa - Branan, Kenyon; Davis, Colin (My University, 2022)
A growing body of work argues that Agree has the effect of “unlocking” certain domains (phases) such that otherwise illicit extraction from them becomes permitted. However, existing proposals disagree on whether Agree is in fact always required to Unlock phases for extraction, or only required for extractions that would otherwise bypass the phase edge. We argue that constraints on extraction from DP in Chichewa reported in Mchombo (2004, 2006) provide evidence for the latter theory, which privileges phase edges. We go on to show that this theory makes correct predictions about Dinka, the language Van Urk & Richards (2015) originally argued provides evidence for the opposite conclusion.
Keywords: Chichewa; Edges and Extraction; Evidence